The Influence of the STEAM Method on the Cognitive Ability of Logical Critical Creative Thinking in Children Aged 5-6 Years - Maulanasari, Devi; Chandra, Ratnasari Dwi Ade; Siswono, Hendrik (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: This study aims to compare the effect of the STEAM method with conventional methods in supporting the development of logical, critical, and creative thinking in children aged 5-6 years. The background of this study is based on the need for a learning approach that can develop high-level thinking skills from an early age, considering that conventional methods are deemed inadequate to support this development. Methodology: The method used is quantitative research with a quasi-experimental approach. The research sample consisted of children aged 5-6 years in kindergarten, divided into two groups: the group using the STEAM method and the group using conventional learning methods. Data collection was conducted through tests assessing logical, critical, and creative thinking abilities before and after treatment. Main Findings: The study's results showed that the application of the STEAM method significantly improved the logical, critical, and creative thinking skills in children aged 5-6 years compared to conventional learning methods. The group using the STEAM method experienced a higher increase in scores on the three aspects of thinking. Novelty/Originality of this study: The discussion in this study confirms that integrating the STEAM method into kindergarten learning can be a practical innovation for developing high-level thinking skills in early childhood. This study implies that educators and policymakers should consider the broader application of the STEAM method in early childhood education as a means to prepare a generation that can think logically, critically, and creatively from an early age.